2013
DOI: 10.1002/etc.2438
|View full text |Cite
|
Sign up to set email alerts
|

Avian, salamander, and forest floor mercury concentrations increase with elevation in a terrestrial ecosystem

Abstract: High-elevation ecosystems of the northeastern United States are vulnerable to deposition and environmental accumulation of atmospheric pollutants, yet little work has been done to assess mercury (Hg) concentrations in organisms occupying montane ecosystems. The authors present data on Hg concentrations in ground-foraging insectivorous songbirds, a terrestrial salamander, and forest floor horizons sampled along a forested elevational gradient from 185 m to 1273 m in the Catskill Mountains, New York, USA. Mean H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 72 publications
(128 reference statements)
2
16
1
Order By: Relevance
“…Earthworm Hg tissue concentrations in our study (0.19 – 0.88 mg kg -1 ) exceeded tissue Hg concentrations in nearly all other terrestrial invertebrates (0.01 – 0.20 mg kg -1 ) reported in Rimmer et al (2010). For example, opportunistic foragers in northern New England, such as red-backed salamanders and Bicknell's Thrush, have been found with inexplicably high Hg tissue and blood concentrations, respectively (Rimmer et al, 2010; Townsend et al, 2014). As a generalist predator, red-back salamanders have been observed to consume large numbers of exotic earthworms (Maerz et al, 2005) and this may be an important Hg source to them and other ground-foraging mammals and birds as well (Talmage and Walton, 1993).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Earthworm Hg tissue concentrations in our study (0.19 – 0.88 mg kg -1 ) exceeded tissue Hg concentrations in nearly all other terrestrial invertebrates (0.01 – 0.20 mg kg -1 ) reported in Rimmer et al (2010). For example, opportunistic foragers in northern New England, such as red-backed salamanders and Bicknell's Thrush, have been found with inexplicably high Hg tissue and blood concentrations, respectively (Rimmer et al, 2010; Townsend et al, 2014). As a generalist predator, red-back salamanders have been observed to consume large numbers of exotic earthworms (Maerz et al, 2005) and this may be an important Hg source to them and other ground-foraging mammals and birds as well (Talmage and Walton, 1993).…”
Section: Discussioncontrasting
confidence: 51%
“…Recent studies describing the terrestrial trophic transfer of mercury in northern New England have not considered earthworms as a potential source (Rimmer et al 2010; Townsend et al 2014). Earthworm Hg tissue concentrations in our study (0.19 – 0.88 mg kg -1 ) exceeded tissue Hg concentrations in nearly all other terrestrial invertebrates (0.01 – 0.20 mg kg -1 ) reported in Rimmer et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, in an assessment of Bicknell's thrush ( Catharus bicknelli ), Swainson's thrush ( Catharus ustulatus ), and Hermit thrush ( Catharus guttatus ) across the deciduous and coniferous zones of Whiteface, Hg blood concentrations increased with elevation, with coniferous zone concentrations nearly twice that of the deciduous zone [ Driscoll and Sauer , ]. Similar findings have been found at other mountains for thrushes and salamanders [ Townsend et al, ]. Thus, songbird Hg concentrations appear to follow patterns in absolute soil MeHg concentration, not relative soil MeHg concentration (%MeHg), and absolute soil MeHg concentrations may be a better indicator of wildlife exposure to MeHg.…”
Section: Discussionmentioning
confidence: 64%
“…Based upon soil characteristics, tree species, precipitation patterns, and expected Hg inputs, ecosystems at higher elevations are thought to receive higher Hg deposition and support greater methylation [ Lawson et al, ; Yu et al, ]. Findings of increased Hg concentrations in invertebrates, salamanders, and birds [ Blais et al, ; Townsend et al, ], along with higher concentration of other contaminants [ Reiners et al, ; Lovett and Kinsman , ; Miller et al, ; Lawson et al, ], with increases in elevation support this hypothesis. Moreover, several studies have also reported higher concentrations of soil THg in coniferous stands compared to deciduous forests [ Kolka et al, ; Graydon et al, ; Fisher and Wolfe , ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the shift to conifer forests with higher elevation also increases Hg deposition via throughfall, as throughfall Hg fluxes under conifers are generally considerably higher than under hardwoods in the Adirondacks (Demers et al, 2007;Blackwell et al, 2014). It is likely that increases in Oa horizon Hg with elevation are also mediated by the shift from hardwood to conifer trees with increasing elevation (Townsend et al, 2014).…”
Section: Geographic Patterns Of Mercury Depositionmentioning
confidence: 98%